Ljudinstallationer i Sveriges utemiljö - Erlandsson, Thomas (SLU/Dept. of Urban and Rural Development, 2010)
When visiting Scaniaparken in Malmö you have the possibility of listening to music streaming out of grass-covered hills. In Helsingborg children can compose their own music and play for their friends on the playground. On a square in Nacka Strand you can hear birds singing in the quiet intervals of trafﬁc. What the places have in common are that they all contain sound installations. All are examples of places where the experience of space can be enhanced by the interpreted sound.